Orbital and Millennial Variations in Sea Ice in the Southwestern Okhotsk Sea Since the Last Interglacial Period and Their Implications - Wang, Anqi; Yao, Zhengquan; Shi, Xuefa; Wang, Kunshan; Zou, Jianjun; Liu, Yanguang; Wu, Yonghua; Gorbarenko, Sergey A. (Frontiers in Earth Science, 2021)
Sea ice in the Okhotsk Sea plays a significant role in global climate change. However, the history and mechanism of changes in sea ice spanning the last glacial cycle remain controversial. In this study, an 8.8 m core (LV55-40-1) was recovered from the southwestern Okhotsk Sea that contains a continuous sea ice record over the past ~110 kyr. The sand fraction and dropstones were used as ice-rafted debris proxies to reconstruct the history of sea ice variations over the last ~110 kyr and to determine the underlying causes on orbital and millennial timescales. Sea ice expansions occurred during MIS 5b, MIS 4, mid-MIS 3, and early MIS 1, which were controlled mainly by decreased autumn insolation on an orbital timescale. Superimposed on the orbital-scale changes, millennial-scale variations in sea ice were also observed, with 19 expansion events that coincided with cold Dansgaard-Oeschger stadials. Millennial scale sea ice variations were most likely controlled by both the Arctic oscillation (AO) and the East Asian summer monsoon (EASM). During periods of negative AO patterns, decreased air temperatures over the Okhotsk Sea caused more active sea ice formation. Such conditions could have been reinforced, by a reduced influence of warm advection at the surface of the Okhotsk Sea caused by decreased discharge from the Amur River that resulted from a weakened EASM during cold stadials.